EFFECT OF CR, DER AND NPM ON CHANGES IN PROFITS IN COAL COMPANIES, PETROLEUM AND GAS - Glorya Laura Silaban; Elsa Romauli Lumban Tobing; Ike Rukmana Sari (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
The study was in the field to measure the effect of changes in the current ratio (CR) or what is often called the debt to equity ratio(DER), and NPM (Profitability ratio) on changes in profits recorded on the BEI for the 2017-2019 timeframe. Our study used a quantitative approach. Because this study's data is based on quantity and statistical data processing, descriptive research is the research method used. Our research used linear regression to examine the results, and this is the method we used. Over 90 coal, oil and gas mining enterprises are represented in the 2017-2019 sample of 49 populations of coal, oil, and gas mining firms. Nonetheless, the components in this researcher's study affect the independent variables as well; however, CR does not affect changes in mining firm profitability. During 2017- 2019, companies listed on the Indonesian Stock Exchange will have a significant effect on coal, oil, and gas prices. Between 2017 and 2019, DER and NPM have a negative influence on the profitability of coal, oil, and natural gas mining companies.